Teachers’ Perception on the Implementation of English Curriculum in SMP Negeri 2 Jeruklegi Cilacap - Syam, Zahriyanda Benti; Saefurrohman, Saefurrohman (Metafora: Jurnal Pembelajaran Bahasa Dan Sastra, 2022)
This paper is aimed to figure out teachers’ perception in SMPN 2 Jeruklegi academic year 2020/2021 on curriculum 2013 implementation. The population of the study were all teachers at school (32 teachers). But the sample were only 30 teacher, since there were some teachers (2 teachers) who did not fill the questionnaire for health reasons. This paper employs descriptive analytic study that used questionnaire as the only instrument in conducting the study. The questionnaire was delivered to all teachers in SMPN 2 Jeruklegi through Google form since in pandemic era, it was almost possible to meet teachers in persons. From the data collection through questionnaire found out that 37% of teachers strongly agreed that curriculum 2013 should be implemented at school, while 63% other teachers stated agreed. It indicated that teachers were enthusiastic by the curriculum 2013 implementation. For curriculum 2013 understanding, almost all teachers (90%) understood about the thematic and scientific approach that used in curriculum 2013, while the other (10%) they stated understand well. From the total teachers (30 teachers), 30% totally agreed and 67% agreed that curriculum 2013 could build students’ character. Deals with book and references, 73% teachers agreed and the remain 27% strongly agreed that the contents of the book and reference break down or detail the competence domains of attitudes, knowledge and skills written in the 2013 curriculum document. In the meantime, there were some problems that faced by the teachers in implementing the curriculum 2013. The facilities and infrastructure available at school (3%), learning media that emphasizes scientific learning (17%) and the IT mastery (10%) were the obstacles for the teachers in implementing the 2013 curriculum.